A trajetória da política de integração em um curso de Enfermagem de uma universidade pública: um estudo de caso - Raissa Silva Souza (2016)
The current study had the objective of analysing the trajectory of curricular integration policies in the different contexts of production in higher education and the meanings given by professors of an undergraduate Nursing Course of a public Federal University of Minas Gerais in its development. This is a qualitative research, a single case study type, for which the theoretical-analytical framework of the policy cycle was selected, where the production of policies is considered dynamic and continuous, unfolded in different playing fields by the definition of the meaning of policies, which are: the context of influence, the context of production and those of practical context. It is argued that the curricular integration policy is a cultural process in which texts and discourses are forged, resulting from the interchange between proposals and curricular practices produced by academic institutions for academic institutions. Thus, it is considered that the meanings produced in the academic context, to which the policies are addressed, are (re) productions that approach and deviate from the original orientations. In the present research, contexts of influence and textual production were accessed through documentary research, expressed in documents produced by different instances involved in the production of curricular policies. The practice context was accessed through semi-structured interviews with twelve professors from two disciplines which had experiences of integration in the curriculum of the Federal University of Minas Gerais (EEUFMG) Nursing Course, namely, Child And Adolescent Nursing and Women's Health. The project of the present study was submitted to the Human Research Ethics Committee, and was approved under the CAAE 011.49912.5.0000.5525. The evidence on integration policy produced in the different contexts was analyzed using the thematic content analysis technique proposed by Bardin. From the data analysis of the first two contexts it can be said that curricular integration is a form of curriculum organization that has been assuming a positive connotation throughout curriculum history, not being a new theme, beginning in the 1920s with the progressive movement of education. It was later used in the 1990s in Brazil and in many other countries, as part of official proposals and international organizations, and as part of the literature disseminated by foreign and Brazilian authors. In accordance with this movement, the curricular policy of the Federal University of Minas Gerais Nursing Course brings academic discourses of authors such as Hilton Japiassu and Ivani Fazenda, with emphasis on the notions of integration as a way to overcome the fragmentation of knowledge and over-specialization; ways of organizing curriculum knowledge; approach that privilege dialogue and articulation between knowledge; posture towards knowledge, consistent with the Brazilian movement for interdisciplinarity. There was a syntony in the way in which the UFMG Nursing School integration in the curricular policy was interpreted in the context of text production and in the context of practice, with slides of meanings from one context to the other, that is, in the UFMG Nursing School texts the integration approaches an Interdisciplinary movement and in the context of the practice, the understanding of the ECA (Child and Adolescent Nursing) and SM (Women's Health) teachers moved between notions that approached multi, pluri and interdisciplinary movements. Upon planning activities for integration, ECA and SM teachers created three teaching activities: the joint lessons, the guiding situation and the seminar, which had the potential to enable interdisciplinary movement, since they favored articulation between knowledge, contents and methods of the disciplines. When implemented, the planning with the potential to promote interdisciplinary movement made multi-disciplinary and interdisciplinary movements possible, for in the implementation of the guiding situation there were disparities in the ways of implementing the activity by teachers, given the complexity of the reality where the teaching took place. The experience of the integration of the disciplines by ECA and SM teachers led them to recognize difficulties and resistance, which were interpreted as part of the change process. Due to all this, it was considered that throughout the course of the curricular integration policy there was a re-signification of the policy, and the different ways of understanding integration shows how much policies are not enshrined in the documents, but on their way to being carried out, constantly reconfigured, given the multitude of possible readings to be made and articulated.